The role of scapular morphological structure in degenerative rotator cuff injury: a digital reconstruction radiograph study - Wen-bin Zhang; Fei-Long Lu; Yu-Lin Ma; Xiao-Ming Du; Hao Song; Zhao-Xi Yang; Yi-Mei Hu (BMC Musculoskeletal Disorders)
Abstract Objective To investigate the relationships among the acromial tilt (AT), the glenoid inclination angle (GIA), the critical shoulder angle (CSA), the acromioglenoid angle (AGA), and degenerative rotator cuff injury via digital reconstruction radiographs (DRRs). Methods A retrospective cohort of 63 patients who met the inclusion criteria were enrolled from the Affiliated Hospital of Chengdu University of Traditional Chinese Medicine between April 2023 and April 2024, 33 patients with rotator cuff injury and 30 controls were included. Clinical data and scapular computed tomography (CT) scans were collected, and three-dimensional reconstructions were generated via Amira software (Thermo Fisher Scientific, USA). Digital reconstruction radiograph (DRR) images were simulated at the Grashey and Y positions of the scapula, and the parameters were measured via Digimizer software (MedCalc Software, Belgium). The diagnostic and predictive validity of each parameter for DRR for rotator cuff injury was assessed through statistical analysis of the measured data, including inter-observer consistency, correlation analysis among parameters, and receiver operating characteristic (ROC) curve analysis. Results (1) Inter-observer reliability was excellent for all the parameters (intra-class correlation coefficient (ICC) > 0.8). (2) CSA and AGA were significantly greater in the rotator cuff injury group (P CSA = 0.003;P AGA < 0.001), whereas GIA was significantly lower (P < 0.001); no difference was detected in AT (P > 0.05). (3) Binary logistic regression analysis revealed that GIA, CSA, and AGA were risk factors for rotator cuff injury (P CSA =0.008; P AGA = 0.001; P GIA = 0.001). (4) ROC analysis yielded area under the curve (AUC) values of 0.755 (GIA), 0.700 (CSA), and 0.796 (AGA), with cutoff thresholds of 83.98°, 30.67°, and 42.04°, respectively. (5) Strong correlations were observed between the CSA and AGA (r = 0.939), whereas the GIA was inversely correlated with both the CSA (r = -0.423) and the AGA (r = -0.471). Conclusion Measurements of GIA, CSA, and AGA derived from DRRs demonstrate high diagnostic value for degenerative rotator cuff injury. DRR represents a reliable alternative to conventional radiography in clinical practice. In the future, DRR holds promise as a tool for assessing the impact of degenerative rotator cuff injury. However, due to radiation exposure concerns, the current application of DRR is recommended primarily for retrospective studies utilizing existing computed tomography (CT) data.